PRODUKSI GLUKOAMILASE DARI RHIZOPUS ORYZAE SKALA FERMENTASI 2 LITER DAN 4 LITER - Linar Z. Udin; Ngadiman Ngadiman; A. T. Karossi (Research Center for Chemistry - LIPI, 1994)
Production of glucoamylase by R. oryzae has been conducted in erlenmeyer flasks using medium containing sago starch as carbon source and soybean meal as nitrogen source. It was known that 2 % of sago starch and 0.5 % of soybean meal in the medium is the best composition for the production of glucoamylase. At the present study, the optimal condition for maximal production of glucoamylase fermentation from R. oryzae was investigated using sago starch medium in the 2L and 4L scale. The results showed that the maximum production of glucoamylase at 600-1500 ml fermentation scale was reached at day-8 of incubation time. At this condition, the enzyme specific activity was 0.85 U/mg protein - 1.50 U/mg protein. Forglucoamylase production within 4000 ml fermentation scale, the maximum enzyme specific activity, 2.58 U/mg protein, was obtained at day-S of fermentation with 300 rpm agitation, while the maximum activity of 3.47 U/mg protein and 4.71 Ulmg protein were achieved at day-6 and day-5 of fermentation process with 500 rpm and 700 rpm agitation, respectively. At this maximum condition, the use of sago starch reached 94 - 98 %, and biomass production at the end of fermentation process was 4.80 - 7.90 g [dry weight)/L medium.